Atypical carcinoid with multiple central airway metastases: A case report. (2021) - Amemiya, Ryosuke; Takada, Ikki; Yazaki, Yuki; Ono, Shotaro; Kou, Keni; Morishita, Yukio; Ikeda, Norihiko; Furukawa, Kinya
Abstract: A 51-year-old man was found to have multiple polypoid tracheal and bilateral main bronchial tumors during postoperative follow-up of atypical carcinoid. He underwent transtracheal biopsy, and was diagnosed as having central airway metastases of the atypical carcinoid. He underwent chemotherapy, but the effects were unfavorable. Owing to the risk of airway obstruction, he was referred to our hospital for interventional bronchoscopy. Carcinoid tumors usually present as peripheral lung lesions or solitary endobronchial abnormalities, but rarely appear as multiple central airway lesions. We present a very rare case of multiple central airway metastases of atypical carcinoid, controlled by bronchoscopic treatment.